P67 Impact of enantiomer-specific maturational changes in pharmacokinetics on the racemic ketorolac target trough concentration. Issue 6 (17th May 2019) - Cloesmeijer, M; Krekels, E; van Esdonk, M; Lynn, A; Smits, A; Tibboel, D; Daali, Y; Olkkola, K; Allegaert, K; Mian, P
Abstract : Introduction: Ketorolac is a racemic drug with analgesic effects specific to its S-enantiomer. This study aimed to describe enantiomer-specific maturational pharmacokinetics (PK). Simulations were performed to describe how S-ketorolac exposure in infants differs from adults, and how this affects the adult racemic analgesic trough threshold EC50 (EC50thr-adult, 0.37 mg/L) in infants (EC50thr-infant )when the same S-target is applied. Methods: A population PK analysis (NONMEM 7.3) was performed based on 1020 plasma samples from 5 studies including 80 patients (adults, children, infants) following single intravenous ketorolac administration. Results: S-ketorolac PK was best described with a 2-compartment model in infants and 3-compartment model in adults, while R-ketorolac PK was best described with a 2-compartment model in all. S-ketorolac clearance [mean population value: 3.45 L/h/56 kg] and central volume of distribution (V1) [4.27 L/56kg] increased exponentially with bodyweight (0.75, 0.59 respectively). R-ketorolac clearance [0.93 L/h/56kg], peripheral volume of distribution (V2) and inter-compartmental clearance (Q) increased exponentially with bodyweight (0.62, 1.20, 0.76 respectively), V1 [4.11 L/56kg] linearly with bodyweight. Simulations revealed EC50thr-adult (0.37 mg/L) contained 0.048 mg/L S-ketorolac as mean in typical adults (BW 48.6–99.6 kg), while EC50thr-adult contained 0.032–0.036 mg/L S-ketorolac in typical infants (BW 5.3–10.6 kg). To reach adult S-enantiomer concentration (0.048 mg/L) in typical infants (BW 5.3–10.6 kg), EC50thr-infant should be 0.49–0.46 mg/L, respectively. Conclusion: Enantiomer-specific maturational PK of ketorolac were described. Subsequent simulations displayed differences in proportion of S- and R-ketorolac on the racemic threshold EC50 . A The same S-ketorolac concentration necessitates a higher EC50thr-infant to EC50thr-adult . Disclosure(s): Nothing to disclose